Pengaruh Kompleksitas Sistem, Kompleksitas Tugas dan Komunikasi Pemakai dan Pengembang Terhadap Kepuasan Pemakai Sistem Informasi Akuntansi pada Bank Syariah di Bandar Lampung - Eferedy, Jhon; -, Kusnadi (Jurnal Riset Akuntansi dan Manajemen Malahayati (JRAMM), 2019)
As advances in accounting information systems continue to be applied, proper applicationof the various information systems must be able to provide satisfaction with the service provided tocustomers. The purpose of this study was to examine the influence of the complexity of the system, thecomplexity of the task and communication to users and developers of user satisfaction in AccountingInformation Systems Islamic Bank in Bandar Lampung. Partial results of analysis there is asignificant effect between system complexity (X1), the complexity of the task (X2), and communicationusers and developers (X3) on user satisfaction SIA (Y) at the Islamic Bank in Bandar Lampung.Simultaneously there is influence between system complexity, task complexity, and communication tousers and developers of user satisfaction SIA (Y) at the Islamic Bank in Bandar Lampung (F value16.886> Ftabel2, 84 or sig. 0.000 <0.05). Retrieved Rsquare 0.535 means 53.5% user satisfactionaccounting information system is described by the variable X and the remaining 46.5% is explained byother causes.Keywords: System Complexity, Task Complexity, User Communication and Development, and UserSatisfaction System